The transverse shear deformation behaviour of magneto-electro-elastic shell - Albarody, Thar M. Badri; Al-Kayiem, Hussain H.; Faris, Waleed Fekry (Springer International Publishing AG, 2016)
Compared to the large number of possible magneto-electro-elastic shell theories, very few exact solutions determining the in-plane stresses, electric displacements and magnetic inductions are possible. While, solving the magneto-electro-elastic shell equations in terms of thermo-magneto-electro-elastic generalized field functions on arbitrary domains and for general conditions exactly are not always possible. In the present work, a linear version of magneto-electro-elastic shell with simply supported boundary conditions, solved exactly, provided that the lamination scheme is cross-ply or anti-symmetric angle-ply laminates. The exact solution that introduced herein can measure the in-plane stresses, electric displacements and magnetic inductions. It also allow for an accurate and usually elegant and conclusive investigation of the various sensations in a shell structure. However, it is important for micro-electro-mechanical shell applications to have an approach available that gives the transverse shear deformation Behaviourfor cases that cannot examine experimentally. An investigated examples were accompanied and noteworthy conclusions were drawn which highlight the issues of the implementation of the exact solution, implication of the effects of the material properties, lay-ups of the constituent layers, and shell parameters on the static Behaviour.